Leaf anatomical features of the Eriosema campestre Benth. (Leguminosae, Papilionoideae, Phaseoleae) complex and potential taxonomic implications - Pacheco Seixas, Diana [UNESP] (2019)
Identification of taxa of the Eriosema campestre Benth. (Leguminosae, Papilionoideae, Phaseoleae) complex has proven difficult due to their morphological uniformity. Eriosema campestre is currently considered to comprise three varieties (E. campestre var. campestre, E. campestre var. delicatula Fortunato and E. campestre var. macrophyllum (Grear) Fortunato), which are mainly distinguished by characters related to hair length and blade morphology of the leaflets, resulting in mistaken identifications of specimens in many herbaria. We analyzed the leaf anatomy of all three varieties of E. campestre in order to acquire potential extra characteristics for their clear delimitation, with an emphasis on the distribution, morphology and histochemical features of glandular trichomes. We recorded peculiarities among the taxa in the leaflet midrib (outline of the midrib and presence/absence of phenolic idioblasts in the phloem) and petiole (organ outline and configuration of the vascular cylinder). We found three morphotypes of glandular trichomes to be common among all three studied taxa, as well as distinct morphotypes for each taxon. Our results suggest that the three taxa of the Eriosema campestre complex represent distinct species, and thus two of them should be elevated to the species category.